Chapter 15 Ageism in Mental Health Assessment and Treatment of Older Adults (2018)
Though it is generally acknowledged that older adults are underserved in the area of mental health services, the impact of ageist stereotypes on mental health diagnosis and access to care, and on the provision of psychotherapy to older adults, has not been extensively studied. This chapter reviews the sparse literature on ageism and mental health services with the goals of examining current practice related to the assessment of mental health problems and barriers to optimal therapy of older adults from the social perspective of ageism. The chapter begins with a review of literature pertaining to attitudes of mental health clinicians towards psychotherapy of older adults, and focuses on possible contributing factors to the development of ageist attitudes among clinicians. Subsequently, we discuss older adults’ negative attitudes toward ageing, psychiatric diagnosis and psychotherapy, which may affect patients’ interpersonal encounters with a psychotherapist. We also address challenges and problems in the assessment and diagnosis of older mental health patients, and raise the possibility that ageist attitudes may be responsible for some of these issues. Finally, we discuss common difficulties in providing therapy to older adults with mental health problems and review different therapy approaches with older adults. Here again, we discuss the possibility that ageist attitudes might play a role in difficulties with the adaptation of these therapeutic methods for older adults. The chapter concludes with a discussion of possible prevention strategies to address ageist attitudes in mental health settings and makes recommendations regarding future research in this understudied area.